Pandangan Ulama Klasik Ibnu Sina dan Ibnu Miskawaih tentang Pendidikan - Sahri (Al-Jadwa: Jurnal Studi Islam, 2022)
Al-qur'an and al-Sunnah are the principles of Islamic education. Thus, it can be understood that the purpose of Islamic education is to unite oneself to Allah. That is, uniting oneself to Allah is the main priority in Islamic education apart from scientific objectives (science and technology, expertise, skills and professionalism), forming human beings to become caliphs, forming noble morals, forming Islamic human beings for oneself and for society, and preparing human beings. for life in this world and the hereafter. When Islamic studies in the West were growing, the study of classical Muslim figures was emphasized. In addition to comparing the theories and thoughts of classical figures and also re-exploring their thoughts which made a very large contribution to education today. Ibn Sina has the view that education must be directed at all the potential that a person has towards perfect development, namely physical, intellectual and moral development. Whereas Ibnu Miskawaih's thoughts in terms of education cannot be separated from his concept of humans and morals.